Enhanced hot electron lifetimes in quantum wells with inhibited phonon coupling - Hamidreza Esmaielpour (Nature Portfolio, 2018)
Abstract Hot electrons established by the absorption of high-energy photons typically thermalize on a picosecond time scale in a semiconductor, dissipating energy via various phonon-mediated relaxation pathways. Here it is shown that a strong hot carrier distribution can be produced using a type-II quantum well structure. In such systems it is shown that the dominant hot carrier thermalization process is limited by the radiative recombination lifetime of electrons with reduced wavefunction overlap with holes. It is proposed that the subsequent reabsorption of acoustic and optical phonons is facilitated by a mismatch in phonon dispersions at the InAs-AlAsSb interface and serves to further stabilize hot electrons in this system. This lengthens the time scale for thermalization to nanoseconds and results in a hot electron distribution with a temperature of 490 K for a quantum well structure under steady-state illumination at room temperature.